2013
DOI: 10.12740/app/19967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolic abnormalities on cognitive performance and clinical symptoms in schizophrenia

Abstract: SummaryAim. The objective of this study is to determine whether and how metabolic abnormalities are associated with clinical symptoms and cognitive performance in schizophrenia. Methods. 46 adult patients with schizophrenia taking first-or second generation antipsychotics were included in the study. The following data were collected: BMI, abdominal circumference, lipid panel and blood glucose, blood pressure and treatment of comorbidities. Clinical symptoms were assessed using PANSS, CDSS, CGI and SAS scales. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…Four studies (Saatcioglu et al, 2016, Sicras-Mainar et al, 2015, Wysokinski, 2013, Pelayo-Teran, 2011 analysing this definition yielded results that show an association between dysglycaemia and schizophrenia symptom severity. Conversely, three studies reported no association between symptom severity and glycaemia, and whilst two of these were of relatively small sample size (Chen et al, 2013, Ogawa et al, 2011, the other featured a relatively larger sample size (Chen et al, 2014).…”
Section: Main Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies (Saatcioglu et al, 2016, Sicras-Mainar et al, 2015, Wysokinski, 2013, Pelayo-Teran, 2011 analysing this definition yielded results that show an association between dysglycaemia and schizophrenia symptom severity. Conversely, three studies reported no association between symptom severity and glycaemia, and whilst two of these were of relatively small sample size (Chen et al, 2013, Ogawa et al, 2011, the other featured a relatively larger sample size (Chen et al, 2014).…”
Section: Main Findingsmentioning
confidence: 99%
“…Overall, eleven studies (Wysokinski, 2013, Takayanagi et al, 2012, Saatcioglu et al, 2016, Sicras-Mainar et al, 2015, Chen et al, 2013, Chen et al, 2014, Ogawa et al, 2011, de Nijs et al, 2016, Dickinson et al, 2008, Gonzalez, 2015, Pelayo-Teran, 2011 were selected for detailed analysis. Tables 1, 2 and 3 demonstrate a comparison of the included studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations